Invincible : ultimate collection. Volume 1 - Kirkman, Robert (Image Comics ; Diamond [distributor], ., 2005)
Presents a collection of the first thirteen issues of the comic "Invincible," in which teenage Mark Grayson, son of the superhero Omniman, struggles to balance girls, peer pressure, and the SATs with his own heroic responsibilities.